METHODS FOR FORMING ORGANIZATIONAL AND MANAGEMENT COMPETENCES OF MASTER’S STUDENTS IN SOCIAL-CULTURAL ACTIVITIES - Khasanova, Gulsanam (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The purpose of the scientific article is to study various ways of forming the organizational and managerial competencies of master’s students in socio-cultural activities, to study the scientific and theoretical views of pedagogue-scientists, as well as to make suggestions. These methods provide a holistic approach to the formation of skills and knowledge necessary for the successful management of socio-cultural activities. Theoretical, comparative, classification and descriptive methods were used to cover the topic of the scientific article.